2013
DOI: 10.1016/j.juro.2013.01.081
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Radiation Exposure in Modern Urological Practice

Abstract: Long-term radiation can lead to cataract formation. However, the accumulated lifetime exposure of the typical urologist may not necessitate further safety precautions, such as lead-lined glasses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 18 publications
0
14
0
2
Order By: Relevance
“…Image quality (spatial resolution and low-contrast sensitivity) were evaluated with a test object FL-18. 7 7 The precision of measurements included the calculation of relative uncertainty with a 95% confidence interval.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…Image quality (spatial resolution and low-contrast sensitivity) were evaluated with a test object FL-18. 7 7 The precision of measurements included the calculation of relative uncertainty with a 95% confidence interval.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…pochodzące ze źródeł medycznych [2][3][4]. Z tego powodu Międzyna-rodowa Agencja Energii Atomowej (International Atomic Energy Agency -IAEA) i Międzynarodowa Komisja Ochrony Radiologicznej (International Commission on Radiological Protection -ICRP) od wielu lat zalecają, żeby osoby wykonujące procedury radiologii interwencyjnej były wyposażone w co najmniej 2 dozymetry indywidualne [5].…”
Section: Wstępunclassified
“…Current occupational guidelines recommend less than 150 mSv per year to the eyes, and the guideline lifetime threshold for cataract formation from ocular radiation exposure is 5,000 mSv [37]. These results indicate that ureteroscopic procedures do not realistically pose an ocular radiation exposure hazard to urologists, based on the level of exposure per case.…”
Section: Radiation Exposurementioning
confidence: 88%
“…Additionally, a recent study of ocular radiation exposure among urologists found that radiation exposure for ureteroscopic procedures ranged from 0.05-0.66 mSv per case [37]. Current occupational guidelines recommend less than 150 mSv per year to the eyes, and the guideline lifetime threshold for cataract formation from ocular radiation exposure is 5,000 mSv [37].…”
Section: Radiation Exposurementioning
confidence: 99%